EX-SITU PREPARED NAFIONâ€“IONIC LIQUID COATED MERCURY FILM ELECTRODE FOR ADSORPTIVE STRIPPING VOLTAMMETRY OF LEAD IN THE PRESENCE OF AMARANTH - Nagles, Edgar Orlando; Arancibia, VerÃ³nica (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Nafion combined with ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM]F3MSO3) coated with mercury film (NLIHgFE) on a glassy carbon electrode modified allowÂ the determine Pb(II)Â by adsorptive stripping voltammetry in the presence of Amaranth (Am).Â Properties of the NLIHgFE were characterizedÂ Â Â by square wave without and in the presence of other ionic liquidÂ´s with different anion where ([EMIM]F3MSO3) showed to be more convenient in the determination the lead compared with other ionics liquids with smaller anions.Â Â Â Â pH 2.6 with buffer Britton-Robinson the complex Am-PbÂ was accumulatedÂ by adsorption on surface of the working electrode at -0.3 V by 80 s.Â and later reduce at negative potential by square wave and current peak appeared at -0.51 V earmarked to the reduction of lead in the complex. The linear calibration curves with ranged from 0.9â€“12.0 ÂµgLâ€“1 for Pb(II). The detection limits (3s) were estimated to be around 0.4 ÂµgLâ€“1 to Pb(II) . The relative standard deviations were 2.0 % at the 4.9 Âµg Lâ€“1 level of Pb(II)Â with 80 s of accumulation (n=7). Other optimal conditions wereÂ (CAm 0.77 Âµmol Lâ€“1; Eads â€“0.3 V; Frecuency 15 Hz and Amplitud pulse 25 mV). The methods were validated using reference materialÂ waste waters (SPSâ€“WW1). Finally, the method was successfully applied to the determination of Pb(II) in tap water after UV digestion.